A Metasurface Beam Combiner Based on the Control of Angular Response - Zhihao Liu (MDPI AG, 2021)
Beam combiners are widely used in various optical applications including optical communication and smart detection, which spatially overlap multiple input beams and integrate a output beam with higher intensity, multiple wavelengths, coherent phase, etc. Since conventional beam combiners consist of various optical components with different working principles depending on the properties of incident light, they are usually bulky and have certain restrictions on the incident light. In recent years, metasurfaces have received much attention and become a rapidly developing research field. Their novel mechanisms and flexible structural design provide a promising way to realize miniaturized and integrated components in optical systems. In this paper, we start from studying the ability of metasurfaces to manipulate the incident wavefront, and then propose a metasurface beam combiner in theory that generates an extraordinary refracted beam based on the principle of phase gradient metasurface. This metasurface combines two monochromatic light incidents at different angles with identical polarization but arbitrary amplitudes and initial phases. The combining efficiency, which is defined as the ratio of the power in the combining direction to the total incident power, is 42.4% at the working wavelength of 980 nm. The simulated results indicate that this proposed method is able to simplify the design of optical combiners, making them miniaturized and integrated for smart optical systems.